Pre-calculus for dummies - Kuang, Yang 1965- (John Wiley & Sons, 2012)
The fun and easy way to learn pre-calculus. Getting ready for calculus but still feel a bit confused? Have no fear. Pre-Calculus For Dummies is an un-intimidating, hands-on guide that walks you through all the essential topics, from absolute value and quadratic equations to logarithms and exponential functions to trig identities and matrix operations. With this guide's help you'll quickly and painlessly get a handle on all of the concepts -- not just the number crunching -- and understand how to perform all pre-calc tasks, from graphing to tackling proofs.
Print version record
Keywords: Precalculus; Mathematics; Calculus; Algebra; Trigonometry; Functions; Calcul infinitésimal; Algèbre; Trigonométrie; Fonctions (Mathématiques); Précalcul; Mathématiques; calculus; algebra; trigonometry; functions (mathematics); mathematics; applied mathematics; MATHEMATICS; Algebra; Intermediate; MATHEMATICS; Essays; MATHEMATICS; Pre-Calculus; MATHEMATICS; Reference